Analisis Semiotika Pierce pada Pertunjukan Tari Dhânggâ Madura - Ulfa Sufiya Rahmah; Sujinah; Ali Nuke Affandy (Institut Teknologi Sepuluh Nopember, 2020)
Dhengge dance embodies the description of fishermen's activities that have asense of beauty that is caused by movement and music produced by the mouth.Human life cannot be separated from signs, and signs always have a load ofmeaning. The symbols contained in this dance were analyzed qualitatively byPierce's semiotics. The costumes of the dancers are interpreted by thefishermen as having a firm attitude and a fighting spirit in facing life, steadfastand tough. Freedom, openness, simplicity, courage, manliness, and persistenceare among the cultural ethos of the Madurese people. The dance movementdepicts a trip to go to sea, search for fish to return to the beach, which meansthat life can be likened to running a boat into the middle of the ocean which attimes is hit by big waves and strong winds, the boat to lose control, losedirection and even sink. For that we need planning, hard work, togetherness, asense of brotherhood and require patience, confidence, persistence, andsurrender.